Tempo, memória e identidade em Os cus de Judas, de António Lobo Antunes - Fonseca, Carlos Henrique [UNESP] (2015)
The novel Os cus de Judas, published in 1979, is part of what the author, António Lobo Antunes, called the learning cycle. At this early stage of his extensive career as a novelist, which highlights the experience by the author in Angola, in the latter years of the Colonial War, are already present some aesthetic, thematic and structural elements to be developed throughout his novelistic production, what ensures its uniqueness in the profitable world of contemporary Portuguese novel. In his fictional construction, Lobo Antunes has memory as a core component of his novels and essays, setting specific times and spaces in which the founding myths of Portuguese identity are put in check. In this sense, our goal is to see how are articulated the concepts of time, memory and identity in order to understand not only the narrative and discursive strategies of the author, but also its relationship to contemporary horizons in the post-modern and post- modernism in Portuguese literature. Therefore, we adopted as a methodology the initial study of the relationship between history, fiction and testimony, followed by a reflection on time, memory and imagination taking as the main reference the studies of Paul Ricoeur. Our research puts forward a reflection on identity in the postcolonial context, comprising the novel as a return of narrative. Finally, our research combines up to studies that show how the literary universe of António Lobo Antunes is paradigmatic of a speech marked by a malaise characteristic of postmodernity, by death, by impossibilities and uncertainties resulting from a traumatic experience, both individual and collective that was the Colonial War